Pengaruh Investasi dan Pertumbuhan Ekonomi terhadap Kemiskinan Provinsi Jawa Barat 2011-2021 - Risqi Nurika Fatha Hidayati; Masruri Muchtar; Pardomuan Robinson Sihombing (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
West Java Province is a province in Indonesia that always shows the realization of foreign and domestic investments that are superior to other provinces in Indonesia. On the other hand, poverty in West Java Province still becomes a main problem as indicated by the high number of people living in poverty. This study aims to determine the effect of investment and economic growth on poverty in West Java Province in 2011-2021. The results show that the high realization of investment has no significant effect on poverty in West Java. However, the high economic growth in West Java has a significant and negative effect on poverty in the area. The government can take the right policies to continue to increase economic growth in West Java and take other steps apart from investing both foreign and domestic investments.